Dependence of cobaltocenium diffusion in ionic liquids on the alkyl chain length of 1-alkyl-3-methylimidazolium cations. Issue 5 (11th January 2016) - Ueda, Hiroyuki; Nishiyama, Katsuhiko; Yoshimoto, Soichiro
Abstract : The electrochemical behavior of cobaltocenium (Cc + ) on a Au(111) electrode was investigated in five 1-alkyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide ([C n mim][Tf2 N], n = 2, 4, 6, 8, or 10) ionic liquids (ILs) in the temperature range from 293.15 to 343.15 K. Abstract : The electrochemical behavior of cobaltocenium (Cc + ) on a Au(111) electrode was investigated in five 1-alkyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide ([C n mim][Tf2 N], n = 2, 4, 6, 8, or 10) ionic liquids (ILs) in the temperature range from 293.15 to 343.15 K by cyclic voltammetry and chronoamperometry. The redox couple of Cc + exhibited a clear reversible one-electron reaction in all the [C n mim][Tf2 N] ILs. The diffusion coefficients of Cc + increased with an increase in the alkyl chain length of [C n mim] + and a decrease in the viscosity of the IL upon elevating the temperature. The viscosity of the IL plays an important role in determining the activation energy for the diffusion of Cc + . The obtained results suggested that the alkyl chain length of [C n mim] + affects the strength of the interaction between Cc + and the surrounding ion species. The results also clarified that the equation proposed by Sutherland adequately describes the diffusion of Cc + in ILs when the effect of the type of IL and the temperature on the product of the Stokes radius of Cc + and the Sutherland coefficient is considered.